The Mechanical Properties of a Smart Compression-Type Isolator Based on Magnetorheological Gel and Magnetorheological Elastomer - Guo-Jun Yu; Xi-Xi Wen; Cheng-Bin Du; Fei Guo (Advances in Materials Science and Engineering)
In order to control the vibration of civil building structures, a smart extrusion-type isolator was developed based on magnetorheological gel (MRG) and magnetorheological elastomer (MRE). The key technology and performance tests of the isolator were investigated as well as the identification of parameters of the mechanical model. Test results showed that the MRG cylinder has a damping characteristic at high frequency while the MRE cylinder has an isolation characteristic at low frequency. The designed isolator is therefore superior over the traditional isolator since it will show small damping and low dynamic stiffness at a high frequency and small amplitude situation, which can overcome stiffness hardening that occurs on the traditional isolator. Meanwhile, the designed isolator will also have the behavior of large isolation and high dynamic stiffness under the low frequency and large amplitude condition, which has the advantage of realizable displacement control. The uniaxial mechanical model for the MRG/MRE smart isolator was built, and the parameters of the designed vibration isolator were identified. Theoretical results obtained from the mechanical model of the MRG/MRE smart isolator agree well with the experimental results indicating that the parameter identification method is feasible and effective.